Workplace loneliness, leader-member exchange and creativity: The cross-level moderating role of leader compassion. (January 2017) - Peng, Jian; Chen, Yushuai; Xia, Ying; Ran, Yaxuan
Abstract: Since previous research on the relation between negative emotions and creativity obtained mixed results, a call has been made for an examination of creativity from the perspective of specific emotions. In response to the call, we studied workplace loneliness—a specific negative emotion that has received little theoretical or empirical attention. We propose a multi-level moderated mediation model in which workplace loneliness inhibits creativity via leader-member exchange and this indirect effect is moderated by leader compassion. Results from a study of 67 teams show that subordinates' workplace loneliness has a negative indirect effect on their creativity through leader-member exchange that is significant, only if, leader compassion is low. These results contribute to the literature on creativity by clarifying why and when workplace loneliness is related to creativity. Highlights: Workplace loneliness inhibited creativity. Leader-member exchange mediated the relation between workplace loneliness and creativity. Leader compassion can buffer the negative effect of workplace loneliness on leader-member exchange. Leader compassion moderated the indirect effect of workplace loneliness on creativity via leader-member exchange.